Exploring Archaism in Translation Theory and Modern Persian Poetics: Towards a Persian Translation Paradigm - Kharmandar, Mohammad Ali (Iranian Journal of Translation Studies, 2015)
The purpose of this study is to explore the position of archaism in Modern Persian poetics and translation theory. Assuming that a considerable number of translation theories have emerged from theorists’ native contextualized determinants, the study emphasizes a more active participation of Persian language in proposing translation theories, models and norms. Providing historical, academic and functional justifications demonstrating the cultural significance of archaism in Iran, the study then situates archaism theoretically within three translation theories, namely hermeneutics, polysystem and postcolonial literature. A basic implication, from the viewpoint of translation theory historiography is that although translation theory is largely dominated by a Western narrative, diverse languages can explore their native potentials in developing translation theories and paradigms. Furthermore, the study suggests that from the first decade of the twenty-first century, the Iranian academic community has been exploring archaic potentials of Persian, showing a rising trend of native self-discovery. Persian scholars, using the arguments in this study, can progressively develop a Persian paradigm of translation.